Rheumatic Valve Disease or Cardiotoxicity. Key Points for Differential Diagnosis - Alvarez-Santana, Ricardo; Escudero-Salamanca, Mara; Garcia-Diaz, Jesus A; Aranda-Fraustro, Alberto; Alexanderson-Rosas, Erick; Espinola-Zavaleta, Nilda (Archives of Clinical and Biomedical Research, 2020)
Abstract not available in the source database.